1989
DOI: 10.1146/annurev.en.34.010189.002401
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of the Deutocerebrum in Insects

Abstract: The deutocerebrum is usually regarded as a preoral neuromere subserving an antennal head segment (81). Most authors agree that it consists of two distinct neuropils (Figure 1): the antennal lobe (AL) and the antennal mechanosensory and motor center (AMMC), also called the dorsal lobe (l0, 17, 35, 39). We adhere to this classical definition, but it should be noted that a different, extended definition of the deutocerebrum has recently been suggested by Strausfeld and coworkers (105, 106). Both areas of the deut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
188
1
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(211 citation statements)
references
References 60 publications
(74 reference statements)
14
188
1
8
Order By: Relevance
“…In M. sexta most of the GABA-ir neurons are LNs, while a small subpopulation belongs to the group of PNs (Hoskins et al, 1986;Homberg et al, 1989). Double labeling with Mas-AT and GABA antisera revealed that in the pupa and in the adult only one Mas-AT-ir type, the LATn, displays additional GABA immunoreactivity.…”
Section: Colocalization Of Mas-at With Gaba Rfamides and A-type Allmentioning
confidence: 96%
“…In M. sexta most of the GABA-ir neurons are LNs, while a small subpopulation belongs to the group of PNs (Hoskins et al, 1986;Homberg et al, 1989). Double labeling with Mas-AT and GABA antisera revealed that in the pupa and in the adult only one Mas-AT-ir type, the LATn, displays additional GABA immunoreactivity.…”
Section: Colocalization Of Mas-at With Gaba Rfamides and A-type Allmentioning
confidence: 96%
“…ORN axons terminate in spherical structures within the AL, called olfactory glomeruli, where they synapse with the neurites of target neurons (local interneurons and projection neurons). Local interneurons process olfactory information within glomeruli and across them, projection neurons relay information processed inside the ALs to the higher brain centers, the mushroom body calyces and lateral horn (Homberg et al 1988(Homberg et al , 1989Stocker 1994;Ito et al 1998;Galizia and Rössler 2010;Galizia 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical sensory afferents terminate in the antennal lobe (AL); whereas, most of exteroceptive mechanosensory afferents terminate in the dorsal lobe (DL) of the brain (Homberg et al, 1989). The AL consists of multiple islets of neurons, known as glomeruli, which can be thought of as the functional units of olfaction.…”
Section: Introductionmentioning
confidence: 99%